HF/E Audit of a Locomotive Remote Control Device. (July 2014) - McDonald, Joseph D.; Kazi, Sadaf; Darling, Cale M.; Durso, Francis T.; Glover, Kenneth A.
Conducting a complete human factors/ergonomics (HF/E) audit of a unique technological device can be complicated. Designing an instrument to aid HF/E practitioners in this process can help to ensure that organizational and operator needs are taken into consideration, relevant HF/E principles are followed, and future audits for similar devices are streamlined. Our team designed such an instrument to evaluate a locomotive remote control device. We provide illustrations of the process cycle and time requirements for each phase to be used as a planning tool for HF/E practitioners who are faced with a similar challenge.